Energy research within the UNFCCC: a proposal to guard against ongoing climate-deadlock. (17th August 2016) - Brook, Barry W.; Edney, Kingsley; Hillerbrand, Rafaela; Karlsson, Rasmus; Symons, Jonathan
Abstract : We propose that an international 'Low-Emissions Technology Commitment' should be incorporated into the United Nations Framework Convention on Climate Change (UNFCCC) negotiation process in order to promote innovation that will enable deep decarbonization. The goal is to accelerate research, development, and demonstration of safe, scalable, and affordable low-emissions energy technologies. Such a commitment should be based on three elements. First, it should operate within existing UNFCCC negotiations so as to encourage developed states to offer directed funding for energy research as part of their national contributions. Second, pledges should be binding, verifiable, and coordinated within an international energy-research plan. Third, expert scientific networks and participating governments should collaborate to design a coordinated global research and technology-demonstration strategy and oversee national research efforts. To this end an Intergovernmental Panel on Low-Emissions Technology Research might be established. This proposal offers some insurance against the risk that the political impasse in international negotiations cannot be overcome. The higher costs associated with low-emissions alternatives to fossil fuels currently creates significant economic and political resistance to their widespread adoption. To breach this impasse, a mechanism supporting accelerated energy research is needed that seeks to reduce future abatement costs, share experience and 'learning-by-doing' in first-of-a-kind demonstrations, and thus facilitate future widespread deployments. These actions will also assist in addressing inequalities in energy access. Policy relevance Over the past decade, global fossil-fuel use and associated carbon emissions have risen steadily, despite the majority of nations agreeing, in principle, to work to limit global warming to less than 2 °C above pre-industrial conditions (IPCC, 2014 ). Accelerated research, development, and demonstration of low-emissions technologies will be required for successful and economically efficient decarbonization of the global economy, but how can the current deadlock be broken? The UNFCCC does not contain adequate mechanisms to promote increased investment in research, so climate-governance institutions are not capturing the gains that could be achieved through a globally coordinated approach. Here, we outline reform proposals that would enhance both the economic effectiveness of global abatement efforts and the political feasibility of accelerated innovation.